Brexanolone (Zulresso): Finally, an FDA-Approved Treatment for Postpartum Depression. Issue 2 (February 2020) - Powell, Jason G; Garland, Scott; Preston, Kayla; Piszczatoski, Chris
Objective: To review the safety and efficacy of brexanolone for the treatment of moderate to severe postpartum depression (PPD).Data Sources: A literature search through PubMed was conducted (January 2012 to July 2019) using the keyword brexanolone for clinical trials published in the English language.Study Selection and Data Extraction: Articles were selected if they were related to the Food and Drug Administration (FDA) approval of brexanolone or provided novel clinical information regarding this drug entity.Data Synthesis: The findings of the review show that brexanolone administered via IV infusion is both an effective and a fairly safe option for the treatment of PPD.Relevance to Patient Care and Clinical Practice: There are several antidepressants currently used to treat PPD; however, this is the first with FDA approval for this indication. The rapid onset of action of brexanolone may offer a quicker relief of these symptoms and may possibly lead to improved quality of life for both the mother and the child.Conclusion and Relevance: The recent FDA approval of brexanolone may offer an effective treatment of moderate to severe PPD and has been shown to rapidly decrease depression symptoms.